2021
DOI: 10.46799/jhs.v2i8.256
|View full text |Cite
|
Sign up to set email alerts
|

Terapi L-Ascorbic Acid 10% dan Glutation 2% Dibandingkan dengan Hidrokuinon 4% pada Pasien Melasm

Abstract: Melasma is a hyperpigmentation disorder that is often found, is chronic. Hydroquinone is considered the standard therapeutic standard of melasma, has limitations and side effects vary. L-ascorbic acid acts as a reactive oxygen species (ROS) scavenger and has the ability to bind copper ions in the tyrosinase workplace. Glutation has the function of depigmentation of the skin that inhibits melanogenesis by suppressing the activity of tyrosinease enzymes. The purpose of this study was to prove and analyze the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
1
0
3
Order By: Relevance
“…Based on previous research by Rinandari et al (2021) where clinical trial research was conducted on humans by administering 4% HQ cream for 8 weeks with MASI (Melasma Area and Severity Index) evaluation to assess the severity of melasma carried out at week 4 and week 8, the melasma lesions experienced significant changes at week 4 and week 8 (Rinandari et al, 2021). Other previous in vitro research found that 0.3% strawberry juice cream (Fragaria ananassa) is a strong antioxidant with an IC 50 antioxidant capacity of 52.59 ppm (Ferdiansyah et al, 2016).…”
Section: Effects Of Administration Of 125% Strawberry Ethanol Extract...mentioning
confidence: 99%
“…Based on previous research by Rinandari et al (2021) where clinical trial research was conducted on humans by administering 4% HQ cream for 8 weeks with MASI (Melasma Area and Severity Index) evaluation to assess the severity of melasma carried out at week 4 and week 8, the melasma lesions experienced significant changes at week 4 and week 8 (Rinandari et al, 2021). Other previous in vitro research found that 0.3% strawberry juice cream (Fragaria ananassa) is a strong antioxidant with an IC 50 antioxidant capacity of 52.59 ppm (Ferdiansyah et al, 2016).…”
Section: Effects Of Administration Of 125% Strawberry Ethanol Extract...mentioning
confidence: 99%
“…Pada penelitian ini didapatkan tingkat pendidikan terakhir terbanyak pada kelompok melasma adalah SMA. Studi lain juga menyatakan pendidikan terakhir pasien melasma yang terbanyak adalah sekolah menengah atas 16 serta studi di Turki yang melibatkan 102 pasien melasma berusia 20-63 tahun mdengan pendidikan subjek penelitian yang paling banyak adalah lulusan SMA. 17 Tingkat pendidikan dikaitkan dengan pengetahuan dan pemahaman mengenai pentingnya perawatan dan perlindungan kulit wajah.…”
Section: Pembahasanunclassified
“…19 Suatu penelitian di India Selatan juga menyebutkan penderita melasma terbanyak adalah IRT dengan prevalensi sebesar 66%. 16 Jika dikaitkan dengan melasma, ibu rumah tangga memperoleh pajanan suhu panas eksternal dalam menjalankan aktivitas rumah tangga, misalnya memasak, memanggang, menyetrika menjemur pakaian, menyapu halaman dan menyiram tanaman. 21 Fotoproteksi yang paling banyak digunakan pada kelompok melasma pada penelitian ini yaitu tabir surya dibandingkan yang menggunakan lebih dari satu fotoproteksi.…”
Section: Pembahasanunclassified
See 1 more Smart Citation